2019
DOI: 10.1590/1516-4446-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length and childhood trauma in Colombians with depressive symptoms

Abstract: Objective:Childhood trauma and telomere length (TL) are important risk factors for major depressive disorder. We examined whether there was an association between childhood trauma and TL in a sample of Colombians who were assessed for depressive symptoms.Methods:We applied the Center for Epidemiologic Studies Depression scale, the Patient Health Questionnaire-9, the Hospital Anxiety and Depression scale and the Childhood Trauma Questionnaire to 92 Colombian subjects (mean age = 21). TL was measured with quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Similarly, in a prospective experimental study in humans, Epel et al (2010) (54) reported increased telomerase activity with greater cortisol level in response to stressors. Jimenez et al (2018) (55) found a positive correlation between T/S ratio and sexual abuse scores in depressive individuals in Latin America.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, in a prospective experimental study in humans, Epel et al (2010) (54) reported increased telomerase activity with greater cortisol level in response to stressors. Jimenez et al (2018) (55) found a positive correlation between T/S ratio and sexual abuse scores in depressive individuals in Latin America.…”
Section: Discussionmentioning
confidence: 97%
“…These infrastructural and logistical requirements are difficult to satisfy when working in settings without extensive medical and laboratory facilities. The few TL studies that have been conducted in LMIC have been mostly limited to hospitals, universities, or other high‐resource settings (eg, Auld et al, 2016; Chatterjee et al, 2015; Eisenberg, Lee, Rej, Hayes, & Kuzawa, 2019; Farrukh, Baig, Hussain, Shahid, & Khan, 2019; Farrukh, Baig, Hussain, & Lucky, 2019; Jiménez, Pereira‐Morales, Adan, & Forero, 2019; Malan, Hemmings, Kidd, Martin, & Seedat, 2011; Oliveira et al, 2018; Pathai et al, 2013; Rej et al, 2019; Tennyson et al, 2018; Von Känel, Malan, Hamer, & Malan, 2015; but see Zahran, Snodgrass, Maranon, Upadhyay, Granger, & Bailey, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Aligned with this important field and its numerous challenges, the Brazilian Journal of Psychiatry has endorsed articles covering “glocal” psychiatric epidemiological research in Brazil and Latin America. Substance use-related disorders,4 the impact of violence and early traumatic experiences on mental health outcomes,5 and health services utilization6 are some of the themes covered in this issue. Psychometric evaluation of screening instruments is also discussed in a number of articles, highlighting the importance of using proper instruments, adequately tested for specific populations, in specific cultural contexts.…”
mentioning
confidence: 99%
“…This partially explains the growing importance of the Brazilian Journal of Psychiatry in the international context. The articles published in this issue represent a wide variety of countries, such as Argentina,8 Colombia,5 and Iran 9. The high quality of the work carried out by the editorial staff and reviewers is being recognized, and the vocation of the Brazilian Journal of Psychiatry as a regional leader, championing local articles with global implications – hence the term glocal used in our title – becomes increasingly evident.…”
mentioning
confidence: 99%